Partisipasi Masyarakat Terkait Konservasi Hutan Mangrove sebagai Penyeimbang Ekosistem di Desa Apar Kota Pariaman - Nadia Syafitri; Nefilinda Nefilinda; Rozana Eka Putri (Journal on Education, 2023)
This research is based on the problems in Apar Village which are the background to the destruction of Mangrove Forests caused by two factors, namely natural factors and human factors. The aim of this research is to analyze and describe 1). Efforts to protect mangrove forests in Apar Village 2). Efforts to preserve mangrove forests in Apar Village 3) Mangrove forests as a balancer for the ecosystem in Apar Village. The type of research used is "mixed methods" research, namely describing and analyzing community participation related to mangrove forest conservation as an ecosystem balancer in Apar Village, Pariaman City. The research was conducted and carried out in Apar Village, Pariaman City. Sample collection techniques are Proportional Random Sampling, according to Observation Data Collection techniques, Questionnaires, Interviews and data analysis techniques used. Descriptive Analysis and Qualitative Analysis (Data Reduction, Data Presentation and Conclusion Drawing The research results were obtained: 1) Efforts to protect mangrove forests in Apar Village, Pariaman City with a percentage value of 74.2% in the "Good" category and seen based on indicators including Ecology with a percentage of 81.7% in the Good Category, Economics with a percentage of 62.7 and social indicators. 78.1 Good category 2) Efforts to preserve mangrove forests in Apar Village. Based on the fact that the percentage of mangrove forest conservation efforts in Pariaman City is 85.14 in the "Very good" category and seen based on indicators including planting participation with a percentage of 75% in the Good Category, Forest Utilization Participation with a percentage of 72% in the Good Category and Indicators of Participation in outreach and training activities with percentage 67% Good Category 3) Mangrove Forests act as a balancer for the ecosystem in Apar Village, including tourist attractions, absorbing carbon dioxide, maintaining climate and weather, a source of animal feed, and a source of community livelihood. Keywords: community participation,mangrove forest conservation, ecosystem balancer